2016
DOI: 10.4103/0301-4738.198844
|View full text |Cite
|
Sign up to set email alerts
|

Retropupillary iris-claw intraocular lens for the surgical correction of aphakia in cases with microspherophakia

Abstract: Purpose:This study aimed to evaluate the safety and efficacy of retropupillary fixation of an iris-claw intraocular lens (IOL; Verisyse polymethyl methacrylate IOL, Abbott Medical Optics [AMO], Netherlands) for the surgical correction of aphakia in microspherophakic eyes without sufficient capsular support.Design:This was a prospective, interventional, noncomparative case series.Methods:This interventional case series comprised 17 eyes of 9 microspherophakic patients. Retropupillary fixation of the Verisyse ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…[2] Recently, interest has been revived in retropupillary fixation of the iris claw lenses in view of their ease of surgery and relatively good results. [89101112131415161718192021222324] The retropupillary fixation of the iris claw lens theoretically reduces the risk of corneal endothelial damage but may be associated with higher incidence of pupillary distortions, glaucoma, and other complications. However, many studies have shown excellent outcomes and have established the effectiveness of this surgical approach in correcting aphakia.…”
mentioning
confidence: 99%
“…[2] Recently, interest has been revived in retropupillary fixation of the iris claw lenses in view of their ease of surgery and relatively good results. [89101112131415161718192021222324] The retropupillary fixation of the iris claw lens theoretically reduces the risk of corneal endothelial damage but may be associated with higher incidence of pupillary distortions, glaucoma, and other complications. However, many studies have shown excellent outcomes and have established the effectiveness of this surgical approach in correcting aphakia.…”
mentioning
confidence: 99%
“…Nevertheless, a convex–concave design has a better safety profile, and a peripheral iridectomy is not required with this design. 17 , 24 , 26 , 28 , 36 , 54 …”
Section: Optic Design Of Iciolmentioning
confidence: 99%
“…Peribulbar, subtenon, or retrobulbar anaesthesia is preferred while implanting ICIOL, as the surgical manoeuvres, including iris-touch and enclavation, may induce pain. 16 , 17 , 21 , 24 , 26 , 36 The pupil should neither be dilated nor constricted. Mohr et al suggested a pupil size of 4–5 mm, optimal for secondary ICIOL implantation.…”
Section: Intraoperative Approachmentioning
confidence: 99%
See 2 more Smart Citations